Assessing conflicts in high-rise stratified buildings in Klang Valley / Nur Fazirah Rashid - Rashid, Nur Fazirah (Faculty of Architecture, Planning and Surveying, 2015)
In the 20th century, our country is developing rapidly and it is good news for Malaysia that wants to be one of the developed countries. In the meantime also, many building was developed as a multi-story building especially high-rise residential building in big cities. Conflicts in high-rise stratified buildings management in Klang Valley are to see the trends of conflicts that always happened in strata building management. The aim of the study is to proposed area of concerns that can be concerned by the stakeholder of Stratified High-Rise Building towards reducing conflicts in Stratified High-Rise Building management. Stakeholder can be referring as Joint Management Body (JMB), Management Corporation (MC), Building Maintenance Agency, and residents of high-rise building. In achieving the aim of the dissertation, three objectives are listed such as to identify the role and duties of Commissioner of Building (COB) in the case study. To investigate the current conflicts occurred in the case study. Lastly, to examine the conflicts reported to Commissioner of Building (COB). The research was conducted in selection of Local Authorities is limited to Local Authority in Klang Valley which is Dewan Bandaraya Kuala Lumpur (DBKL), Majlis Badaraya Petaling Jaya (MBPJ), Majlis Bandaraya Shah Alam (MBSA), Majlis Perbandaran Subang Jaya (MPSJ), and Majlis Perbandaran Klang (MPK). This research is the platform to discuss and deliberate data collection and outcomes from the semi structured interview with COB Officer and documents review from data collection.